2020
DOI: 10.1002/jcb.29845
|View full text |Cite
|
Sign up to set email alerts
|

PARK7 enhances antioxidative‐stress processes of BMSCs via the ERK1/2 pathway

Abstract: Oxidative stresss in the microenvironment surrounding lesions induces apoptosis of transplanted bone-marrow-derived mesenchymal stem cells (BMSCs). Hence, there is an urgent need for improving antioxidative-stress processes of transplanted BMSCs to further promote their survival. The present study reports the role and mechanism of Parkinson's disease protein 7 (PARK7) in enhancing antioxidative activity in BMSCs. We used a PARK7 lentivirus to transfect BMSCs to up-or downregulate PARK7, and then used H 2 O 2 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In addition, Parkinson’s disease protein 7 (PARK7) is an antioxidant protein that enhances cellular resistance to oxidative stress and stress-induced apoptosis ( 180 , 181 ). PARK7 overexpression enhances antioxidative‐stress capacity in BMSCs via activating the ERK1/2 signal pathway, which effectively decreases the level of ROS/malondialdehyde and protects the mitochondrial membrane potential as well as inhibits apoptosis of BMSCs subjected to oxidative stress ( 160 ). Moreover, PARK7 can also promote the disintegration of Nrf2/Kelch-like echinacoside associated protein 1 complex, thereby activating Nrf2.…”
Section: Enhancing the Effect Of Bmscsmentioning
confidence: 99%
“…In addition, Parkinson’s disease protein 7 (PARK7) is an antioxidant protein that enhances cellular resistance to oxidative stress and stress-induced apoptosis ( 180 , 181 ). PARK7 overexpression enhances antioxidative‐stress capacity in BMSCs via activating the ERK1/2 signal pathway, which effectively decreases the level of ROS/malondialdehyde and protects the mitochondrial membrane potential as well as inhibits apoptosis of BMSCs subjected to oxidative stress ( 160 ). Moreover, PARK7 can also promote the disintegration of Nrf2/Kelch-like echinacoside associated protein 1 complex, thereby activating Nrf2.…”
Section: Enhancing the Effect Of Bmscsmentioning
confidence: 99%
“…Cyclosporin A had been shown to increase the viability of trophoblast cells and reduce the ROS-induced oxidative injury by the inhibition of the p38 pathway ( He et al, 2020 ). Overexpression of Parkinson’s disease protein 7 prevented the oxidative stress-induced apoptosis of transplanted BMSCs by the activation of the ERK1/2 pathway ( Zhang et al, 2021 ). Curcumin could attenuate oxidative stress and cardiomyocyte apoptosis to improve the cardiac function in streptozoticin-induced type 2 diabetic rats by the activation of the PI3K/AKT/mTOR pathway in vivo ( Ren et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, how CORM-3 ameliorates oxidative stress-induced damage is unclear. In the present study, oxidative stress was induced in BMSCs using H 2 O 2 as previously reported [ 21 ].…”
Section: Introductionmentioning
confidence: 70%